INTEGRATED USE OF PRE AND POST EMERGENCE HERBICIDES FOR EFFECTIVE WEED MANAGEMENT AND ENHANCED YIELD OF CASTOR (Ricinus communis L.) - perumal, veeramani; S MANICKAM; K SUBRAHMANIYAN; M VELMURUGAN; M RAJESH; R VIJAYAN; A GOPIKRISHNAN; T BALAJI (The Indian Journal of Agricultural Sciences, 2026)
Castor oil is an industrially significant product that serves as a chemical platform for the production of numerous products and their derivatives, including sebacic acid. Although the output of castor (Ricinus communis L.) is still significantly hampered by weed competition, resulting in 28 - 30 % yield losses. At TCRS, Yethapur, this study sought to assess the effectiveness of herbicides on rainfed castor throughout the Kharif seasons of 2022–2023 and 2023–2024. The experiment comprised 12 treatments: one weed-free check, one weedy check, one mechanical weed management, and nine herbicide treatments. The herbicide treatments included three pre emergence (PE) applications (Diclosulam, Metribuzin, and Pendimethalin), one early post-emergence (EPOE) (Imazethapyr), and one post emergence herbicide (POE) (Quizalofop ethyl), arranged in three replications with RBD. The trial field was ruled by sedge infestations in both years, followed by dicot and grassy weeds. The PE spray of diclosulam 84% WDG at 20 g/ha on 3 DAS, trailed by an EPOE of imazethapyr 10% SL at 100 g/ha on 15 DAS, and supplemented with power weeding on 30 DAS, generated the least amount of weeds of 3.24, 3.84, and 4.06 weeds/m² at 25, 50, and 75 DAS, respectively, according to the two-year study’s pooled mean data. The total dry weight of weed was recorded as 2.24, 2.87, and 3.51 g/m² at 25, 50, and 75 DAS, in that orderThe highest weed control index (WCI) was reported by this combination of 83.8, 83.9 and 84.8% on 25, 50, and 75 DAS, respectively, with corresponding weed control efficiency (WCE) values of 76.7, 76.5 and 83.2%, respectively, respectively. With a castor yield of 1735 kg/ha, a net revenue of Rs. 75540/ha, and a benefit cost ratio (BCR) of 2.64, this treatment produced the lowest weed index (4.9%), the highest herbicide efficiency index (6.93%), and the lowest weed persistence index (0.46). Following this, diclosulam 84% WDG was applied PE on 3rd DAS @ 20 g/ha. On 15 DAS, Imazethapyr 10% SL was applied as an EPOE herbicide @ 100 g/ha, and on 30 DAS, quizalofop ethyl 5% EC was applied POE @ 50 g/ha. The No.of spikes per plant (13.9), effective spike length (57.7 cm), yield of castor (1779 kg/ha), net revenue (Rs. 77760/ha), and BCR (2.69) were all higher after power weeding at 20, 40, and 60 DAS.